2014
DOI: 10.1146/annurev-biophys-051013-022950
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Conserved RNA Secondary Structure in Transcriptomes and Genomes

Abstract: Transcriptomics experiments and computational predictions both enable systematic discovery of new functional RNAs, but many putative noncoding transcripts arise instead from artifacts and biological noise, and current computational prediction methods have high false positive rates. I discuss prospects for improving computational methods for analyzing and identifying functional RNAs, with a focus on detecting signatures of conserved RNA secondary structure. An interesting new front is the application of chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(159 citation statements)
references
References 134 publications
(199 reference statements)
4
155
0
Order By: Relevance
“…Despite these advances, the accuracy of RNA structure inference through chemical mapping and sequencing remains under question (3)(4)(5)(6)(7)(8). For example, models of the 9-kb HIV-1 RNA genome have been repeatedly revised with updates to the selective 2′-OH acylation by primer extension (SHAPE) protocol, data processing, and computational assumptions (2,(9)(10)(11), and the majority of this RNA's helices remain uncertain.…”
mentioning
confidence: 99%
“…Despite these advances, the accuracy of RNA structure inference through chemical mapping and sequencing remains under question (3)(4)(5)(6)(7)(8). For example, models of the 9-kb HIV-1 RNA genome have been repeatedly revised with updates to the selective 2′-OH acylation by primer extension (SHAPE) protocol, data processing, and computational assumptions (2,(9)(10)(11), and the majority of this RNA's helices remain uncertain.…”
mentioning
confidence: 99%
“…Chemical modification by DMS or other probes can be rapidly read out at every nucleotide of an RNA through primer extension reactions that terminate immediately 3′ to the modified bases, followed by electrophoresis or next-generation sequencing of the resulting cDNA products. The currently available set of chemical and enzymatic probes of RNA structure and methodological accelerations have been described in several recent reviews (Eddy, 2014;Kwok et al 2015;Weeks, 2010) and these methods continue to be advanced (see, e.g. Kielpinski & Vinther, 2014;Poulsen et al 2015;Spitale et al 2015). )…”
Section: Prelude: 1d Rna Chemical Mappingmentioning
confidence: 99%
“…For example, reanalysis of a model based on selective 2´-OH acylation by primer extension (SHAPE) of the 9173-nucleotide HIV-1 RNA genome (Watts et al 2009) suggested that more than half of the presented helices were not well-determined (Kladwang et al 2011c), and subsequent work, including both experimental and computational improvements, have significantly revised these uncertain regions (Pollom et al 2013;Siegfried et al 2014;Sukosd et al 2015). The debate over whether these methods produce acceptable structure accuracies continues (Deigan et al 2009;Eddy, 2014;Kladwang et al 2011c;Leonard et al 2013;Rice et al 2014;Sukosd et al 2013;Tian et al 2014) and will not be reviewed in detail here. There is general agreement, however, on some points.…”
Section: Prelude: 1d Rna Chemical Mappingmentioning
confidence: 99%
See 2 more Smart Citations